UHPLC Q-Exactive MS-Based Serum Metabolomics to Explore the Effect Mechanisms of Immunological Activity of Astragalus Polysaccharides With Different Molecular Weights - Li, Ke; Cui, Lian-Jie; Cao, Yu-Xin; Li, Shu-Ying; Shi, Li-Xia; Qin, Xue-Mei; Du, Yu-Guang (Frontiers in Pharmacology, 2020)
Astragalus polysaccharides (APS) have a wide range of biological activities. Most researchers discuss total APS as the main research object. However, because the relative molecular weight of APS has a wide distribution, in-depth studies on the mechanisms of the biological activity of notable molecules are limited. For example, the relationship between the immunomodulatory effect of APS and its relative molecular weight has not been clearly defined. Therefore, in this paper, we separated and obtained APS of different molecular weights by ultrafiltration technology and then constructed a mouse cyclophosphamide immunosuppression model to investigate the immune activity of APS of different molecular weights. The immune enhancement mechanism of APS was explored by examining changes in routine blood indicators, body weight, immune organs, and differential metabolites in mouse serum. Results showed that APS-I (molecular weight, >2000 kDa), APS-II (molecular weight, 1.02×104 Da) and APS-III (molecular weight, 286 Da) could increase the number of immune cells in mouse serum and improve immune organ damage to varying degrees. Among the samples obtained, APS-II showed the best effects. Compared with those in the blank group, 29 metabolites determined by UHPLC Q-Exactive MS in the serum of the model group changed remarkably, and APS-I, APS-II, and APS-III respectively restored 13, 25, and 19 of these metabolites to normal levels. Metabolomics analysis revealed that APS-II is mainly responsible for the immunomodulatory activity of APS. Metabolomics analysis revealed that the mechanisms of this specific molecule may involve the regulation of phenylalanine metabolism, cysteine and methionine metabolism, tricarboxylic acid cycle (TCA cycle), and arginine and proline metabolism.